Data gathering, surveillance and human rights: recasting the debate. Issue 2 (2nd July 2016) - Bernal, Paul
ABSTRACT: The nature and depth of internet surveillance has been revealed to be very different from what had previously been publically acknowledged or politically debated. There are critical ways in which the current debate is miscast, misleading and confused. Privacy is portrayed as an individual right, in opposition to a collective need for security. Data gathering and surveillance are portrayed as having an impact only on this individual right to privacy, rather than on a broad spectrum of rights, including freedom of expression, of assembly and association, the prohibition of discrimination and more. The gathering and surveillance of 'content' is intrinsically more intrusive than that of 'communications' data or 'metadata'. The impact of data gathering and surveillance is often portrayed as happening only at when data are examined by humans rather than when gathered, or when examined algorithmically. Commercial and governmental data gathering and surveillance are treated as separate and different, rather than intrinsically and inextricably linked. This miscasting has critical implications. When the debate is recast taking into account these misunderstandings, the bar for the justification of surveillance is raised and a new balance needs to be found, in political debate, in law, and in decision-making on the ground.